Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting